FEASIBILITY STUDY OF LAHAT, TALANGAKAR, AND GUMAI FORMATION AS SHALE GAS SOURCE ROCK BASED ON ORGANIC GEOCHEMISTRY AND BRITTLENESS INDEX ANALYSIS - SAUNG PENGGALIH , MUHAMMAD
The research area is in Tebo Regency, Jambi Province, southeast of Bukit Tigapuluh National Park. Geologically the study area belongs to the Jambi Subbasin, South Sumatra Basin. This study used 35 shale samples for organic geochemical analysis, 18 shale samples for XRD analysis, 13 shale samples for SEM analysis, and 9 coal samples for organic petrography analysis. All samples are outcrop samples. The formations studied were three, namely, Gumai Formation, Talangakar Formation, and Lahat Formation. Geochemical analysis has been carried out to determine the quantity, quality, and maturity of the source rock. XRD and SEM analyses were done to determine the value of BI. Organic petrography analysis was carried out to determine the depositional environment. The results of geochemical analysis showed that the Gumai Formation has TOC of 0.91-1.42%; kerogen type III; and immature. The Talangakar Formation has a TOC of 0.81-20.42%; kerogen type III dominance; early mature (45%). The Lahat Formation has a TOC level of 0.59-27.18%; kerogen type I, II, III; early mature (55%). The value of BI Gumai Formation is 47.7%; Talangakar Formation 51.7%; and Lahat Formation 36.6%. The depositional environment of the Gumai Formation is the open sea, the Talangakar Formation is the transition zone – open sea, and the Lahat Formation is terrestrial – transition zone. Based on the comparative results of shale gas geological characteristics of North American and Sichuan Basin, the three formations are worthy of being the source rock for the low maturity petroleum gas shale system.